The Provocative Joan Robinson The Making of a Cambridge Economist - Aslanbeigui, Nahid (Duke University Press, 2009)
One of the most original and prolific economists of the twentieth century, Joan Robinson (1903-83) is widely regarded as the most important woman in the history of economic thought. Robinson studied economics at Cambridge University, where she made a career that lasted some fifty years. She was an unlikely candidate for success at Cambridge. A young woman in 1930 in a university dominated by men, she succeeded despite not having a remarkable academic record, a college fellowship, significant publications, or a powerful patron. In The Provocative Joan Robinson, Nahid Aslanbeigui and Guy Oakes trace the strategies and tactics Robinson used to create her professional identity as a Cambridge economist in the 1930s, examining how she recruited mentors and advocates, carefully defined her objectives, and deftly pursued and exploited opportunities.